Pengendalian Inflasi, Moneter dan Fiskal dalam Perspektif Ekonomi Makro Islam - Saiyed, Rahmah (P3M STIEM, 2021)
Abstrack : The economic development of a country, including in Indonesia, is inseparable from the monetary and fiscal policies adopted by each country. But the several of monetary and fiscal policies adopted by each country are dependent on the real economic conditions, direction and development goals to be achieved. The management of monetary and fiscal policy are basically aimed to maintain the level of inflation by regulating the circulation of money and interest rates that tend to increase in the community. The aim of this study is to find out how the government can control inflation, monetary, and fiscal, as well as their impact on the economy in an Islamic macroeconomic perspective. This research uses the library research method and the data used is secondary data that derived from the number of relevant literatures. In an effort to stablize the inflation, monetary and fiscal policies, the govenrment is very important to undertake macroeconomic policies in relation with the inflation target and economic growth. Therefore, each country needs to maintain economic stability in accordance with the challenges it faces